Effects of silencing dishevelled 1, 2 and 3 mRNA expression on MDA-MB-231 cell migration and invasion using siRNAs - Khoo, Samuel Leon Juan (2015)
The Wnt signalling pathway plays an important role in embryonic development, generation of cell polarity and specification. Previous studies have shown that both canonical and non-canonical Wnt signaling pathways are involved in breast cancer metastasis. Dishevelled, one of the components of both canonical and non-canonical Wnt signaling pathway is involved in proliferation, polarity, terminal differentiation and self-renewal of cells. It is well known that Dishevelled interacting with Axin plays a role in dissociating the β-catenin destruction complex in the canonical Wnt signaling pathway. Although the involvement of Dishevelled in the non-canonical Wnt signaling pathway is less well studied compared to the canonical pathway, the role of Dishevelled is also important for cytoskeletal reorganization in planar cell polarity pathway and promoting tissue separation as well as ventral axis identity in Xenopus via the Wnt Calcium pathway. Our hypothesis is that silencing of human Dishevelled 1,2 and 3 isoforms results in inhibition of both canonical and non-canonical Wnt signaling pathway leading to reduced β-catenin interaction with TCF (T-cell Factor) and LEF (Lymphoid Enhancer Factor), reduced cell proliferation, migration and also invasion regardless of canonical or non-canonical Wnt signaling pathway. MDA-MB- 231 is the breast cancer cell line used in this study. The objectives in this study include (1) to confirm the silencing of Dishevelled 1,2 and 3 by reverse-transcription quantitative PCR and Western Blotting. (2) to determine the changes in cell viability, migration, invasion, TCF-LEF mediated transcriptional activation after gene silencing using siRNA targeting Dishevelled isoforms. (3) to identify the changes in β-catenin, Glycogen Synthase Kinase-3β (GSK3β) protein, Epidermal Growth Factor Receptor (EGFR) and Extracellular signal-Regulated Kinases (ERK) expression in cells transfected with siRNAs targeting Dishevelled 1, 2 and 3. This study resulted in a few interesting findings: (1) A significant reduction of Dishevelled 1,2 and 3 mRNA levels in cells transfected with siRNA based on reverse transcription quantitative PCR was observed. However, we were not able to detect Dishevelled 1 isoform at the protein level using the commercially available anti-Dishevelled 1 antibody; (2) different phenotypical changes were observed in cells transfected with siRNA targeting Dishevelled 1 and Dishevelled 2. This occurred with siRNA D1_9 or siRNA D2_4 where cells transfected with both siRNAs showed reduced cell viability. However, there was no significant change in cell viability, migration and invasion with other siRNAs for Dishevelled 1 and Dishevelled 2 siRNA (D1_6 and D2_8, respectively) as compared to control. Further studies showed that both siRNAs D1_9 and D2_4 resulted in reduced cell invasion and migration that were statistically significant. This indicates that there is possibility of target non-specificity by both siRNAs and for siRNA D2_4 or it could also be due to a higher degree of Dishevelled 2 knockdown. (3) Dishevelled 3 plays a role in mediating Wnt3a-stimulated TCF-LEF transcriptional activity. Reduced Wnt3a-stimulated TCF-LEF transcriptional activation was observed in MDA-MB-231 cell line transfected with siRNAs targeting Dishevelled 3 especially on cells transfected with siRNA D3_7 which was found to be statistically significant. (4) both densitometric results of phospho-GSK3β- Serine 9 expression (relative to total GSK3β) and phospho-β-catenin expression (relative to total β-catenin) for cells transfected with Dishevelled 3 siRNAs shows that a higher expression of phospho- GSK3β-Serine 9, which is indicative of inactive GSK3β, can result in reduced β- catenin degradation (phospho-β-catenin). However, the level of β-catenin degradation (relative to total β-catenin) expression in Dishevelled 3 siRNA transfected cells was comparable to Control. The basal phospho-β-catenin in Dishevelled 3 siRNA transfected cells was not related to GSK3β activity in this study. (5) by relating both phospho-β-catenin expression (relative to total β-catenin) on densitometric analysis and Luciferase assay, reduced β-catenin degradation results in a higher TCF-LEF activity for cells transfected with siRNA targeting Dishevelled 1 and 2. However, reduced TCF/LEF mediated transcriptional activity in cells transfected with Dishevelled 3 siRNAs did not show an increase in phospho-β-catenin expression (relative to total β-catenin) as compared to control. Silencing of Dishevelled 3 expression maintains expression of basal phospho-β-catenin, which is sufficient for degradation or dissociation of β-catenin destruction complex resulting in the reduced TCF/LEF mediated transcriptional activity. It is possible that disruption of the interaction between Dishevelled 3 but not Dishevelled 1 and 2 with Axin interferes with formation of β-catenin destruction complex formation resulting in reduced TCF/LEF-sensitive transcriptional activity by Wnt3a in MDA-MB-231 cells or interference at the promoter binding site for β-catenin/ TCF-LEF complex. (6) densitometric analysis of Western Blot involving components along EGFR-ERK pathway shows that Wnt3a stimulation does not result in activation of EGFR-ERK pathway and knockdown of Dishevelled isoforms do not result in reduction of EGFRERK pathway under Wnt3a stimulation. In conclusion, Dishevelled 3 is involved in canonical Wnt β-catenin pathway in MDA-MB-231 breast cancer cells, playing a role in inhibiting proteosomal degradation of β-catenin. It is possible that knockdown of Dishevelled 3 expression disrupted the interaction with Axin, reduced β-catenin accumulation and ultimately reduced Wnt3a stimulated TCF/LEF-mediated transcriptional activity. It is possible that silencing of Dishevelled 3 expression interfered with β-catenin/TCF-LEF-mediated transcriptional activity. On the contrary, non-reduction in β-catenin/ TCF-LEF-mediated transcriptional activity and low phospho-β-catenin expression relative to total β-catenin in Dishevelled 1 and Dishevelled 2 siRNA transfected cells suggest that Dishevelled 1 and 2 isoforms are not involved in canonical Wnt β-catenin pathway on MDA-MB-231 cell line.